Case Report: Hemodynamic challenges during the anesthetic management of a patient who presented with a cervical vagal schwannoma in southern Ethiopia: a rare clinical case - Ilala, Tajera Tageza; Ayano, Gudeta Teku; Kebede, Mengistu Yinges (Frontiers in Surgery, 2025)
BackgroundVagal schwannoma is a benign tumor formed from the Schwann cells of the vagus nerve. Therefore, surgery is a viable treatment option for patients requiring tumor excision. However, anesthetic management of patients presenting with vagal schwannoma may pose a significant challenge to anesthetists because of an increased risk of intraoperative hemodynamic instability, cardiac arrhythmias, and postoperative functional impairment of the vocal cords, resulting in a life-threatening airway compromise.Case descriptionA 68-year-old female patient was referred to the otorhinolaryngology outpatient department of our institution with a history of lateral left neck swelling for 2 years, which started incidentally and gradually increased to attain the current size. CT of the neck revealed a schwannoma of the vagus nerve. General anesthesia was induced with propofol and succinylcholine following adequate preparation and premedication for surgical excision of the vagal schwannoma. She developed hemodynamic instability (a sudden decrease in her heart rate from 109 beats/min to 54 beats/min) and significant hypotension (her arterial blood pressure dropped from 168/87 mmHg to 78/36 mmHg) 30 min after the surgery. These symptoms were successfully treated with an intravenous injection of atropine sulfate (0.5 mg) and volume expanders, followed by vasopressor support (100 mcg intermittent bolus dose of epinephrine per 5 min twice), and the surgeon stopped the traction on the vagus nerve. The patient was awakened, extubated, and successfully transferred to the post-anesthesia care unit at the end of the procedure. No complications occurred during the post-operative period, and home discharge was made on day 4 of the post-operative period.ConclusionResection of a vagal schwannoma may pose significant challenges to the anesthetist during the intraoperative course due to the manipulation of the vagus nerve, mimicking the risk of hemodynamic instability. Hence, anesthetists should conduct adequate preoperative assessment and evaluation, be properly prepared, and closely monitor for and aggressively manage any hemodynamic instability to reduce morbidity and mortality during the resection of a vagus nerve schwannoma.